Green synthesis, characterization, and electrochemical behavior of gold nanoparticles on boron-doped diamond electrode - Wiyogo Prio Wicaksono; Aushofin Hamidah (Chemistry Education Program, the University of Mataram, 2018)
Gold nanoparticles (AuNPs) have been successfully synthesized through a single-step bioreduction method using Piper betle leaf extract (PBLE) as a green reducing and stabilizing agent. Their formation was confirmed by UV-Visible spectroscopy, resulted in a characteristic Surface Plasmon Resonance (SPR) peak at 545 nm, whereas there is no peak observed in the extract. By using Particle Size Analyzer (PSA), it has been characterized that they have a 100 nm diameter. For characterizing electrochemical behavior, the cyclic voltammetry technique was applied in a various range of electrolyte condition (HCl 0.1M, NaCl 0.1M, phosphate buffer 0.1M pH 7, and NaOH 0.1M). The best oxidation and reduction peak of the AuNPs were obtained in HCl at 0.93 V and 0.68 V, respectively. This green synthesized AuNPs could be applied as a label in immunochromatographic strip tests for various sensing applications.